Amundsen's route to the South Pole - Drewry, David John; Huntford, Roland (Polar Record, 1979)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Scott and Amundsen - Huntford, Roland (Hodder & Stoughton, 1979)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

Prosessering av sonarbøyedata fra Antarktis - Hvidsten, Johannes (Universitetet i Bergen, Seismological Observatory, 1979)
Keywords: Antarktis; seismologi

Naturressurser i Antarktis: av særlig interesse for Norge - Mobæk, Are; Østgård, Jon; Børset, Erik; Karlsen, Bernt Stilluf; Larsen, Thor (Miljøverndepartementet, 1979)
Keywords: Antarktis; polarområdene; ressurser

Flow of Antarctic ice shelves between long. 29° E. and 44° W - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: Antarktis; glasiologi; innlandsis; isfront; isshelf; isstrøm; kalving

Ice-shelf underwater morphology - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: Antarktis; NARE 1976/77; ekspedisjoner; forskning; glasiologi; isshelf; morfologi

Trends and prospects for regimes for living and mineral resources in Antarctica - Sollie, Finn (Stiftelsen, 1979)
Keywords: Antarktis; politikk; ressurser

Trends and prospects for regimes for living and mineral resources in the Antarctic + discussion - Sollie, Finn (Law of the sea: neglected issues - proceedings, Law of the Sea Institute twelfth annual conference, October 23-26, 1978, The Hague, 1979)
Keywords: Antarktis; forvaltning; jus

Sydpolen - Amundsen, Roald; Lindberg, Odd F (Niloe, 1978)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Scott's transport 1911-1912 - Jones, A G E (Polarboken, 1978)
Keywords: Antarktis; ekspedisjoner; historie; logistikk

Polarområdenes økosystemer - Larsen, Thor (1978)
Keywords: Antarktis; polarområdene; økologi

Norsk polarpolitikk ut av tåkeheimen - Leistad, Geirr I (Farmand, 1978)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene; polarpolitikk

Biota of the antarctic pack ice: R/V Hero cruise 77-5 - Siniff, D.; Laws, R.; Oritsland, T.; Stirling, I.; Bengtson, J.; Demaster, D.; Reichle, R. (Antarctic Journal of the United States, 1978)
Between 22 October and 20 November 1977, we used National Science Foundation's R/v Hero to conduct studies of Antarctic seals in pack-ice areas of the Antarctic Peninsula. Our principal focus was on crabeater seals, but we also were interested in other pack-ice species, particularly leopard seals. Our work centered on (a) collecting female crabeater and leopard seals for reproductive material depicting various stages of the reproductive cycle, (b) documenting further the social structure and reproductive behavior of crabeater seals, (c) observing daily activity patterns and local movements of crabeater seals at fast-ice concentrations, and (d) investigating crabeater seal behavior at weaning and their interaction with leopard seals.
Keywords: Antarktis; Sørishavet; marin biologi; seler

Kuldetoleranse hos alpine og arktiske collemboler - Sømme, Lauritz (Entomologisk tidskrift, 1978)
Keywords: Antarktis; ekspedisjoner; entomologi; forskning; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Antarctica : or two years amongst the ice of the South Pole - Nordenskjöld, Otto; Andersson, Johan Gunnar; Skottsberg, Carl; Larsen, Carl Anton; Fuchs, Vivian (Hurst, 1977)
Keywords: Antarctic (skip); Antarktis; Carl Anton Larsen; Den svenske antarktisekspedisjonen 1901–03; Otto Nordenskjöld; vitenskapelige ekspedisjoner

Global glacier mass balance variations during the past 300 years - Orheim, Olav (Arctic Institute of North America, 1977)
Keywords: Antarktis; glasiologi; is; isbreer; klimaendringer; konferanse; polarområdene; stratigrafi; symposium

Med "Polarsirkel" til Antarktis! - Orheim, Olav (Rieco-nytt, 1977)
Keywords: Antarktis; Bouvetøya; ekspedisjoner; reisebeskrivelser

Food Consumption of Seals in the Antarctic Pack Ice - Øritsland, Torger (Smithsonian Institution, 1977)
Keywords: Antarktis; biologi; dyreliv; havis; seler; sjøis; zoologi

Antarktis-traktaten, ressursene og utnyttelsen - Sollie, Finn (Stiftelsen, 1977)
Keywords: Antarktis; jus; politikk; ressurser

Norges ansvar i Antarktis - Sollie, Finn (Stiftelsen, 1977)
Keywords: Antarktis; politikk; ressurser

Kåre Holts bok om Roald Amundsen (Polarboken, 1976)
Keywords: Antarktis; litteratur

Antarktis - Antonsen, Per (Norske interesser i polarområdene, 1976)
Keywords: Antarktis; ekspedisjoner; polarområdene

Naturrseurser i Antarktis - Antonsen, Per (Norske interesser i polarområdene, 1976)
Keywords: Antarktis; ressurser; økonomi

En glemt polaforsker: Carsten Egeberg Borchgrevink - Evans, Hugh B; Jones, A G E (Polarboken, 1976)
Keywords: Antarktis; biografi; ekspedisjoner; historie

Hva gjør Norge i Antarktis? - Orheim, Olav (Norske interesser i polarområdene, 1976)
Keywords: Antarktis; ekspedisjoner; forskning; politikk

Antarktis i fokus - hva gjør norsk forskning? - Orheim, Olav (Forskningsnytt, 1975)
Keywords: Antarktis; NARE ekspedisjoner; geologi; glasiologi; havis; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; polarområdene

Past and present mass balance variations and climate at Deception Island, South Shetland Islands, Antarctica - Orheim, Olav (International Association of Hydrological Sciences, 1975)
Keywords: Antarktis; forskning; glasiologi; klimatologi

Naturressursene i Antarktis - Antonsen, Per (Internasjonal politikk, 1974)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; ressurser

A forgotten explorer: Carsten Egeberg Borchgrevink - Evans, Hugh B; Jones, A G E (Polar Record, 1974)
Keywords: Antarktis; biografi; ekspedisjoner; forskning; oppdagelsesreiser

Some notes on the future of the Antarctic Treaty collaboration - Hambro, Edvard (American journal of international law, 1974)
politikk jus
Keywords: Antarktis

The South Pole - Mountfield, David (A history of polar exploration, 1974)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Glaciological studies in the South Shetland Islands - Orheim, Olav (Antarctic Journal of the United States, 1974)
Keywords: Antarktis; Sør-Shetlandsøyene; geofysikk; glasiologi

Antarktis i sikkerhetspolitisk perspektiv - Skagestad, Odd Gunnar (Internasjonal politikk, 1974)
Keywords: Antarktis; politikk

Vitenskapelig utforskning som internasjonalt samarbeidsprosjekt i polarområdene - Skagestad, Odd Gunnar (Stiftelsen, 1974)
Keywords: Antarktis; forskning; jus; politikk

Antarktis og den internasjonale havbunnsorganisasjon - Traavik, Kim (Internasjonal politikk, 1974)
Keywords: Antarktis; Antarktistraktaten; havbunnen; havrett; internasjonal; politikk; ressurser; rett

Antarctic resources: report form the informal meeting of experts 30 May - 9 June 1973 (Fridtjof Nansen-stiftelsen på Polhøgda, 1973)
Keywords: Antarktis; forskning; jus; politikk; ressurser

Svalbard - Jan Mayen - The Antarctic Possessions (Utenriksdepartementet, 1973)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

Virksomheten i Arktis og Antarktis - Gjelsvik, Tore ([Norsk Polarinstitutt], 1973)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; marinbiologi; polarforskning; politikk

Antarktis, i fare for forurensing, som mulig dumpeplass for radioaktivt kjernefysisk avfall - Lund, Thoralv (Polarposten, 1973)
Keywords: Antarktis; miljøvern; radioaktivitet

Hvem bestemmer hva i Antarktis? - Rey (Polarposten, 1973)
Keywords: Antarktis; jus; politikk

The Antarctic: 'troubles' revisited - Skagestad, Odd Gunnar (Bulletin of peace proposals, 1973)
Keywords: Antarktis; politikk

The duration of the Antarctic treaty: an analysis of the amendment and revision procedures in a political perspective - Sollie, Finn (Stiftelsen, 1973)
Keywords: Antarktis; jus; politikk

Analyse av tidejordsmålinger på Sydpolen - Syrstad, Erik (Universitetet i Bergen, 1973)
Keywords: Antarktis; geologi

Isfjell kan brukes til overrisling - Haraldsen, Gunnar (Polarposten, 1972)
Keywords: Antarktis; isfjell; teknologi

Byrd's South Pole Flight - 1929-30 - Isakson, Evelyn Moore (Bernt Balchen, colonel, United states Air force, retired : a special report on the unique career of a great American patriot, 1972)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Saga of the white horizon - Olsen, Magnus L (Nautical Publishing Co., 1972)
Keywords: Antarktis; Lincoln Ellsworth; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner; transantarktiske flyturen

Opprettelsen av Antarktistraktaten av 1959 : en forhandlingsteoretisk analyse - Sand, Turid (Fridtjof Nansen-stiftelsen, 1972)
Keywords: Antarktis; statsvitenskap

Forurensing av polarområdene? Et spørsmål om regulering av utviklingen - Sollie, Finn (Internasjonal politikk, 1972)
Keywords: Antarktis; Antarktistraktaten; forurensning; internasjonal; miljø; politikk; økologi

En reise til Sydpolskontinentet "Antarktis" (Polarposten, 1971)
Keywords: Antarktis; Sørishavet; turisme

Report on attendance at the Second Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6 to 15 August, 1970 - Kent, L E (Geological Survey of South Africa, 1971)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Sydpolisen opptil 4000 m tykk: Sydpollandet har 95 pst. av isen i verden! - Lund, Thoralv (Polarposten, 1971)
Keywords: Antarktis; forskning

Antarktis i sikkerhetspolitisk perspektiv - Skagestad, Odd Gunnar (Internasjonal politikk, 1971)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; ressurser; rett

Abstracts of papers presented at Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6-15 August 1970 (SCAR/IUGS, 1970)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

The Last of "The Ten". Antarctic Pioneer Still Lives On (Antarctic, 1970)
Keywords: Antarktis; Hugh Blackwall Evans; Southern Cross; biografi; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; overvintring

Antarktistraktaten: en ny type internasjonal organisasjon - Engh, Ulf (Stiftelsen, 1970)
Keywords: Antarktis; jus; politikk

De konsultative møter under Antarktistraktaten - Hanevold, Truls (Stiftelsen, 1970)
Keywords: Antarktis; jus; politikk

Antarktis uten ispanser - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; geofysikk; geologi

Ønske om fortsatt Antarktis-innsats - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; politikk

Tolv lands polarforskere til Antarktis-møte i Oslo - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; forskning

Glaciological investigations on Deception Island - Orheim, Olav (Antarctic Journal of the United States, 1970)
Keywords: Antarktis; glasiologi

Energetic significance of absorption of solar radiation in polar homeotherms - Øritsland, Nils Are (Antarctic ecology, 1970)
Keywords: Antarktis; fysiologi; seler; stråling; zoofysiologi